Gastrointestinal Disorder Associated with Olmesartan Mimics Autoimmune Enteropathy. - Sophie Scialom; Georgia Malamut; Bertrand Meresse; Nicolas Guegan; Nicole Brousse; Virginie Verkarre; Coralie Derrieux; Elizabeth Macintyre; Philippe Seksik; Guillaume Savoye; Guillaume Cadiot; Lucine Vuitton; et al. (PLoS ONE, 2015)
Background and objectives Anti-hypertensive treatment with the angiotensin II receptor antagonist olmesartan is a rare cause of severe Sprue-like enteropathy. To substantiate the hypothesis that olmesartan interferes with gut immune homeostasis, clinical, histopathological and immune features were compared in olmesartan-induced-enteropathy (OIE) and in autoimmune enteropathy (AIE). Methods Medical files of seven patients with OIE and 4 patients with AIE enrolled during the same period were retrospectively reviewed. Intestinal biopsies were collected for central histopathological review, T cell Receptor clonality and flow cytometric analysis of isolated intestinal lymphocytes. Results Among seven olmesartan-treated patients who developed villous atrophy refractory to a gluten free diet, three had extra-intestinal autoimmune diseases, two had antibodies reacting with the 75 kilodalton antigen characteristic of AIE and one had serum anti-goblet cell antibodies. Small intestinal lesions and signs of intestinal lymphocyte activation were thus reminiscent of the four cases of AIE diagnosed during the same period. Before olmesartan discontinuation, remission was induced in all patients (7/7) by immunosuppressive drugs. After interruption of both olmesartan and immunosuppressive drugs in six patients, remission was maintained in 4 but anti-TNF-α therapy was needed in two. Conclusion This case-series shows that olmesartan can induce intestinal damage mimicking AIE. OIE usually resolved after olmesartan interruption but immunosuppressive drugs may be necessary to achieve remission. Our data sustain the hypothesis that olmesartan interferes with intestinal immuno regulation in predisposed individuals.